[Brizziolari Creek Watershed] - John H. Klopp::::::photographer::: (1949)
On front: "Brizziolari Creek Watershed in part, top center of photo estimated 1000 acres. Drumm Lake (Reservoir) center left. Diversion ditch to start above junction of field area and creek."